A Study of Service Quality and Customer Satisfaction across Various Service Providers in the Telecom Sector - Joshi, Sandhya (Indian Journal of Marketing, 2011)
The telecommunications market, in the last few years, has seen incredible technological advancement, which has fueled massive consumer adoption and brutal competition driven by commoditization. To drive profits in this business, you must increase the average lifetime value per customer and minimize the service cost, even as service choices increase. Common to all of our customers in the telecom sector is an abiding belief in delivering the best service to customers by investing in technology that empowers consumers and service agents to have intelligent, productive conversations. In a marketplace, where consumers are increasingly aware of their choices, consistent service quality is the foundation of a durable brand. In this paper, a survey of the selected customers has been done in order to know whether they are satisfied with the service quality of various service providers considered for this study. Attempt has been made to know that how customers rate the services of various service providers taken for this study.